Analysis of the Influence of Coach Communication on Team Performance in Team Sports - Siregar, Mufidah Armindy; Dilly Ana Damayanti; Apulta Purba; Yosevin Silaban (Universitas Negeri Jakarta, 2025)
This study aims to analyze the influence of coach communication on the performance of team sports teams by considering the mediating role of coach-athlete relationships. The design of a correlational quantitative research with 300 athletes from 30 team teams (soccer, volleyball, basketball). The instruments used included the Coach Communication Scale (α = 0.892), the Coach-Athlete Relationship Questionnaire (α = 0.876), and the Team Performance Scale (α = 0.845). The analysis used multiple regression and bootstrap mediation (5,000 samples). Coach communication had a positive effect on team performance (β = 0.38, p < 0.001), with the coach-athlete relationship as a partial mediator (Indirect effect = 0.12, CI 95% [0.06–0.19]). Effective coach communication improves team performance directly as well as through quality interpersonal relationships. Adaptive and empathy-based communication strategies can be used as the basis for coach development programs to increase the effectiveness of team sports teams.